2020
DOI: 10.1111/apa.15612
|View full text |Cite
|
Sign up to set email alerts
|

Infections and nutritional status of internationally adopted children in France

Abstract: Aim In the context of global changes in the epidemiology of internationally adopted children (IACs), the prevalence of infectious diseases and nutritional impairment has not been recently reviewed. Moreover, in France, these characteristics of the children according to their continents of origin and preadoption special needs (SN) status have been incompletely explored. Methods Demographic, infectious data and anthropometric of all the newly arrived IACs seen in a specialised clinic for international adoptees i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It is an important clinical and public health problem among children and adolescents associated with adverse health outcomes at all stages of human life and may reflect food poverty (Ieiri et al 2021), unhealthy eating habits (Rawal et al 2021), or an increased risk of many diseases. Underweight children and adolescents are more likely to suffer from infectious diseases (Goutines et al 2021), have reduced cognitive functions (Suryawan et al 2021), mental disorders (Donkor et al 2021;Zeiler et al 2021) and have low scores your health (Linardon et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is an important clinical and public health problem among children and adolescents associated with adverse health outcomes at all stages of human life and may reflect food poverty (Ieiri et al 2021), unhealthy eating habits (Rawal et al 2021), or an increased risk of many diseases. Underweight children and adolescents are more likely to suffer from infectious diseases (Goutines et al 2021), have reduced cognitive functions (Suryawan et al 2021), mental disorders (Donkor et al 2021;Zeiler et al 2021) and have low scores your health (Linardon et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In other observational studies, the rates of recovery of parasites ranged from 9% to over 70% [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was similar in children with and without gastrointestinal symptoms and with and without malnutrition. In most studies, giardiasis was the most commonly identified parasitic infection, with as many as 19 percent of children infected [ 24 , 25 , 26 , 27 , 28 , 29 ]. Helminthic infections are less common (<3 percent), with Hymenolepis species , Ascaris lumbricoides , and Trichuris trichiura most often reported.…”
Section: Discussionmentioning
confidence: 99%
“…There is a consensus that internationally adopted children should be evaluated by pediatricians with experience in the eld. Most protocols agree on the importance of a thorough medical history upon arrival, an exhaustive physical examination, and complementary tests, followed by completion of the immunization schedule 10,11 . In children with SN, the particular conditions of each individual case should be considered, and patients should be referred to specialists for proper multidisciplinary management 2, .…”
Section: Discussionmentioning
confidence: 99%